List zastawny na niemieckim rynku finansowym - Półtorak, Bogusław (Role and Meaning of Mortgage Bonds on German Financial Market, 2005)
Mortgage bonds were essential instrument on the mortgage market in Germany. Mortgage bonds were an important instrument on financial market. They were a substantial element of the financial debt market. A law on mortgage bonds and mortgage banks (which came into force on 13 July 1899) constituted existence of long-term credit institutions, such as mortgage banks. Currently 20 mortgage banks are present in German. They hold together ca. 21% in mortgage credits funded by commercial bank sector.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 105-114